Creative God, colorful us - Newbell, Trillia J. (Moody Publishers, 2021)
"God could have made us all exactly the same, but He didn't. And our differences are good! This short, colorful book (written with grade-schoolers in mind) will share the truth about how we were made, our differences, our sin problem, God's rescue, and how we should be motivated to love one another on earth"--